Why hospital design matters: A narrative review of built environments research relevant to stroke care. Issue 4 (April 2022) - Bernhardt, Julie; Lipson-Smith, Ruby; Davis, Aaron; White, Marcus; Zeeman, Heidi; Pitt, Natalie; Shannon, Michelle; Crotty, Maria; Churilov, Leonid; Elf, Marie
Healthcare facilities are among the most expensive buildings to construct, maintain, and operate. How building design can best support healthcare services, staff, and patients is important to consider. In this narrative review, we outline why the healthcare environment matters and describe areas of research focus and current built environment evidence that supports healthcare in general and stroke care in particular. Ward configuration, corridor design, and staff station placements can all impact care provision, staff and patient behavior. Contrary to many new ward design approaches, single-bed rooms are neither uniformly favored, nor strongly evidence-based, for people with stroke. Green spaces are important both for staff (helping to reduce stress and errors), patients and relatives, although access to, and awareness of, these and other communal spaces is often poor. Built environment research specific to stroke is limited but increasing, and we highlight emerging collaborative multistakeholder partnerships (Living Labs) contributing to this evidence base. We believe that involving engaged and informed clinicians in design and research will help shape better hospitals of the future.